Intraperitoneal alpha therapy with 224Ra-labeled microparticles combined with chemotherapy in an ovarian cancer mouse model - Wouters, Roxanne; Westrøm, Sara; Berckmans, Yani; Riva, Matteo; Ceusters, Jolien; Bønsdorff, Tina B.; Vergote, Ignace; Coosemans, An (Frontiers in Medicine, 2022)
A novel alpha-therapy consisting of 224Ra-labeled calcium carbonate microparticles (224Ra-CaCO3-MP) has been designed to treat micrometastatic peritoneal disease via intraperitoneal (IP) administration. This preclinical study aimed to evaluate its efficacy and tolerability when given as a single treatment or in combination with standard of care chemotherapy regimens, in a syngeneic model of ovarian cancer in immune competent mice. Female C57BL/6 mice bearing ID8-fLuc ovarian cancer were treated with 224Ra-CaCO3-MP one day after IP tumor cell inoculation. The activity dosages of 224Ra ranged from 14 to 39 kBq/mouse. Additionally, 224Ra-CaCO3-MP treatment was followed by either carboplatin (80 mg/kg)-pegylated liposomal doxorubicin (PLD, 1.6 mg/kg) or carboplatin (60 mg/kg)-paclitaxel (10 mg/kg) on day 14 post tumor cell inoculation. All treatments were administered via IP injections. Readouts included survival, clinical signs, and body weight development over time. There was a slight therapeutic benefit after single treatment with 224Ra-CaCO3-MP compared to the vehicle control, with median survival ratios (MSRs) ranging between 1.1 and 1.3. The sequential administration of 224Ra-CaCO3-MP with either carboplatin-paclitaxel or carboplatin-PLD indicated a synergistic effect on overall survival at certain 224Ra activities. Moreover, the combinations tested appeared well tolerated in terms of weight assessment in the first four weeks after treatment. Overall, this research supports the further evaluation of 224Ra-CaCO3-MP in patients with ovarian cancer. However, the most optimal chemotherapy regimen to combine with 224Ra-CaCO3-MP should be identified to fully exploit its therapeutic potential.